Chorea as the First and Only Manifestation of Systemic Lupus Erythematosus - Abdul Razzakh Poil; Fahmi Yousef Khan; Abdo Lutf; Mohammed Hammoudeh (Case Reports in Rheumatology)
We report a case of right-sided hemichorea associated with systemic lupus erythematosus (SLE) in a female patient who presented with involuntary movements of hand and foot, without any other manifestation of SLE. Further workup showed positive tests for antinuclear antibody, anti-Smith antibody, anti-dsDNA, and antiphospholipid antibody (aPL). The patient was started on aspirin and hydroxychloroquine and her chorea resolved after three weeks of followup. This is one of the few reported cases of SLE where chorea is presented as the first and only manifestation of SLE.